Advances in the Functional Nucleic Acid Biosensors for Detection of Lead Ions. (17th February 2023) - Zhang, Bu-yue; Shi, Lei; Ma, Xiao-ying; Liu, Lu; Fu, Yao; Zhang, Xiu-feng
Abstract: Lead ions (Pb 2+ ) are destructive to the natural environment and public health, so the efficient detection of Pb 2+ is particularly important. Although the instrumental analysis methods have high accuracy, they require high cost and precise operation, which limits their wide application. Therefore, many strategies have been extensively studied for detecting Pb 2+ by biosensors. Functional nucleic acids have become an efficient tool in this field. This review focuses on the recent biosensors of detecting Pb 2+ based on functional nucleic acids from 2010 to 2020, in which DNAzyme, DNA G-quadruplex and aptamer will be introduced. The biosensors are divided into three categories that colorimetric, fluorometric and electrochemical biosensors according to the different reported signals. The action mechanism and detection effect of each biosensor are explained. Finally, the present situation of nucleic acid biosensor for the detection of Pb 2+ is summarized and the future research direction is prospected.